Photonics: Concept, Devices and Applications - Agarwal, P.C.; Arya, V.P. (SCHOOL SCIENCE, 2015)
Sense of vision is very important for all of us, as it is our window to the world. Light coming from objects after reflection or scattering facilitates our eyes to observe the objects and hence the entire world with the help of light. We cannot imagine about the world without light. As study of polity is politics and study of economy is economics; in the same way, study of photon (light) is the photonics. The term ‘Photonics’ can be understood in close analogy with the familiar term of electronics. Electronics involves control of electric charge flow whereas photonics involves the control of photons in vacuum or in matter. Photonics reflects the growing tie between optics and electronics forged by the increasing role that semiconductor materials and devices play in optical systems.